Cultural Values Represented in First Certificate Masterclass Taught in Iran - Zahra Alimorad (SAGE Open, 2016)
Due to the crucial role textbooks play in any educational system, an urgent need is felt to examine, evaluate, and choose the most suitable ones available. This study is an attempt to critically examine and uncover the hidden curriculum in First Certificate Masterclass (FCM) that is taught at Navid institute in Iran. To this aim, FCM was deeply examined to identify any instances of Western cultural norms and preferences and their potential influences on Iranian EFL (English as a Foreign Language) learners’ thoughts and ideologies. Peterson’s distinction between Big “C” culture and little “c” culture constituted the theoretical framework of the study. To collect the necessary data, all passages, texts, exercises, and even listening excerpts were closely studied and evaluated by the researcher. Results indicated that among the elements of little “c” culture introduced by Peterson, preferences or tastes, food, hobbies, popular music, and popular issues could mainly be observed in the book. Furthermore, the majority of the representations introduced and depicted in the book were incompatible with Iranian Muslim people’s ideologies and beliefs. Implications of these findings for Iranian material developers and textbook writers as well as English teachers are also discussed.